Preparation of pure, high titer, pseudoinfectious Flavivirus particles by hollow fiber tangential flow filtration and anion exchange chromatography. Issue 35 (20th August 2015) - Mundle, Sophia T.; Giel-Moloney, Maryann; Kleanthous, Harry; Pugachev, Konstantin V.; Anderson, Stephen F.
Highlights A purification procedure for a replication-deficient flavivirus is described. Purification is achieved by tangential flow filtration followed by anion exchange chromatography. The use of a convective monolithic anion exchanger supports recovery of infectious virus. Purification results in ∼60% recovery of infectious virus titer. Vaccine virus with titers as high as 1 × 109 FFU/mL have been prepared.